Wrapped into sound: Development of the Immersive Music Experience Inventory (IMEI) - Wycisk, Yves; Sander, Kilian; Kopiez, Reinhard; Platz, Friedrich; Preihs, Stephan; Peissig, Jürgen (Frontiers in Psychology, 2022)
Although virtual reality, video entertainment, and computer games are dependent on the three-dimensional reproduction of sound (including front, rear, and height channels), it remains unclear whether 3D-audio formats actually intensify the emotional listening experience. There is currently no valid inventory for the objective measurement of immersive listening experiences resulting from audio playback formats with increasing degrees of immersion (from mono to stereo, 5.1, and 3D). The development of the Immersive Music Experience Inventory (IMEI) could close this gap. An initial item list (N = 25) was derived from studies in virtual reality and spatial audio, supplemented by researcher-developed items and items extracted from historical descriptions. Psychometric evaluation was conducted by an online study (N = 222 valid cases). The N = 222 Participants (female = 112, mean age = 38.6) were recruited via mailing lists (n = 34) and via a panel provider (n = 188). Based on controlled headphone playback, participants listened to four songs/pieces, each in the three formats of mono, stereo, and binaural 3D audio. The latent construct “immersive listening experience” was determined by probabilistic test theory (item response theory, IRT) and by means of the many-facet Rasch measurement (MFRM). As a result, the specified MFRM model showed good model fit (62.69% of explained variance). The final one-dimensional inventory consists of 10 items and will be made available in English and German.